O efeito do treinamento muscular inspiratório associado ao uso da oxandrolona na função muscular respiratória de indivíduos com doença neuromuscular - Nunes, Luciana Ortenzi [UNIFESP] (2006)
Purpose: to evaluate the effects of inspiratory muscle training (IMT) associated to anabolic steroid oxandrolone in pulmonary function of patients with neuromuscular diseases. Methods: Fourteen subjects (9 male, 5 female, mean age 36±17 years) with the following diseases: limb-girdle muscular dystrophy (n=9), Becker muscular dystrophy (n=1), facioescapulohumeral muscular dystrophy (n=1) and spinal muscular atrophy (n=3), performed the following assessments: maximal static inspiratory and expiratory pressures (respectively, MIP and MEP), maximal voluntary ventilation in 12 seconds (MVV), respiratory muscle resistance (RMR) and spirometry. The research included four evaluations: baseline, after 30 days of IMT at 40% of baseline MIP, after 30 days of washout and after 30 days of IMT (at 40% of MIP) associated with oxandrolone (0.1 mg/kg/day). Results: MIP and MEP increased after IMT (p<0,05), and after washout they returned to baseline levels. MIP, MEP and RMR were higher after oxandrolone was associated to IMT (p<0,05), but a reduction in dynamic pulmonary volumes (FVC, FEV1 and FEF25-75%) was found in this condition (p<0,05). Conclusion: The association of oxandrolone increased the effect of the IMT, however, although to have occurred fall in some variables analyzed in the spirometry, we do not observe alteration in the ventilatory functional diagnosis, in all the studied patients.